An Analysis of Character Values in English Textbook for Seventh Grade Students Entitled When English Rings The Bell (Revised 2016) - Aprisa Marise Aminingsi (Jadila: Journal of Development and Innovation in Language and Literature Education, 2021)
This study aims to investigate the values of characters in the 2013 curriculum in English textbook students at seventh grade students entitled "When English Rings a Bell (Revised 2016)" used by secondary schools in Bengkulu. This research uses content analysis techniques. in addition semi-structured interviews with English teachers were conducted teacher perceptions about character education and English textbooks in their schools. The results showed that the most dominant percentage of character values ​​among the eighteen character values ​​are related to self with a very large majority percentage which obtained that are discipline values ​​with the percentage (6.39%), hard work (3.83%), Curiosity (1.22% ), Independence (0.56%), Honestly (0.44%), Creativity (0.44%), Reading interest (0.22%), Responsibility (0.11%). Then it was followed Related to Others that are Friendship / Communicative (2.11%), Achievement Appreciation (0.39%), Tolerance (0.22%), democracy (0.11%), Love of peach (0.06%) and followed Related to God, religiosity (1.22%). There was a small amount of Related to Environment (Environmental awareness (0.28%), Social cares (0.17%), and related to nation (Nationalism (0.28%), Patriotism (0.06%). Almost all character values ​​have been applied in the English textbook.The conclusion is that the textbooks used by secondary students’ for seventh grade in Bengkulu worth used, but for the future must pay more attention to the character values ​​in accordance with the competency standards of graduates with current student development.